Separation of binary mixtures based on gamma infinity data using [OMMIM][BF4] ionic liquid and modelling of thermodynamic functions. (February 2019) - He, Zhuang-Zhuang; Miao-Zhang,; Ge, Ming-Lan; Jiao, Yu-Hai; Zhao-Mu,; Yi, Yu-Feng; Ding, Fu-Chen
Graphical abstract: Highlights: Measurements of activity coefficients at infinite dilution using GLC. The (gas-liquid) partition coefficients were calculated. The excess thermodynamic functions, enthalpies, entropies, and Gibbs energies were calculated. The solubility parameter of the IL [OMMIM][BF4 ] was determined. Selectivity and capacity for hexane ( i )/benzene ( j ), cyclohexane ( i )/benzene ( j ). The linear free energy relationship (LFER) analysis of the results was performed. Abstract: The activity coefficients at infinite dilution ( γ i ∞ ), gas-liquid partition coefficients ( K L ) of organic solutes ( n -alkanes, alkenes, alkyl benzenes, acetonitrile, acetone, tetrahydrofuran, ethyl acetate, 1, 4-dioxane, chloromethanes, alcohols and cycloalkene) in the ionic liquid 1-octyl-2, 3-dimethylimidazolium tetrafluoroborate ([OMMIM][BF4 ]) have been measured using the gas-liquid chromatographic method (GLC) at five temperatures (313.15 K–353.15 K). The density of [OMMIM][BF4 ], as a function of temperature, was determined in atmosphere pressure p = 101.3 kPa. The values of the partial molar excess enthalpies at infinite dilution ( H - i E, ∞ ) were derived from the temperature dependence of the l n γ i ∞ values at a reference temperature T ref = 298.15 K. The entropies ( T ref S - i E, ∞ ) and Gibbs free energies ( G - i E, ∞ ) of organic solutes in [OMMIM][BF4 ] at a reference temperature T ref = 298.15 K were calculated from the γ i ∞ values. The Hildebrand's solubility parameters of [OMMIM][BF4 ] were determined by the regular solution theory (RST) combined with Flory ''combinatorial'' equation. The interaction between the IL and the individual solutes can be disclosed and the nature of force for IL was explored by the linear free energy relationship (LFER) analysis. Selectivity ( S ij ∞ ) and capacity ( k j ∞ ) at infinite dilution at 323.15 K have been determined for n -hexane ( i )/benzene ( j ), cyclohexane ( i )/benzene ( j ). The results were analysed in comparison to literature data for alkylimidazolium ionic liquids (ILs) with [ B F 4 ] - .